Adjustable current-induced magnetization switching utilizing interlayer exchange coupling - Sheng, Yu; Edmonds, Kevin; Ma, Xingqiao; Zheng, Houzhi; Wang, Kaiyou (Wiley-VCH, 2018)
Electrical current-induced deterministic magnetization switching in a magnetic multilayer structure without external magnetic field is realized by utilizing interlayer exchange coupling. Two ferromagnetic Co layers, with in-plane and out-of-plane anisotropy respectively, are separated by a spacer Ta layer, which plays a dual role of inducing antiferromagnetic interlayer coupling, and contributing to the current-induced effective magnetic field through the spin Hall effect. The current-induced magnetization switching behavior can be tuned by pre-magnetizing the in-plane Co layer. The antiferromagnetic exchange coupling field increases with decreasing thickness of the Ta layer, reaching 630 ±5 Oe for a Ta thickness of 1.5nm. The magnitude of the current-induced perpendicular effective magnetic field from spin-orbit torque is 9.2 Oe/(107Acm-2). The large spin Hall angle of Ta, opposite in sign to that of Pt, results in a low critical current density of 9×106A/cm2. This approach is promising for the electrical switching of magnetic memory elements without external magnetic field.